Mycobacterium tuberculosis protein Rv2652c enhances intracellular survival by inhibiting host immune responses - Jihong Li; Yafeng Dou (Immunity, Inflammation and Disease)
Abstract Backgrounds Mycobacterium tuberculosis (Mtb), the pathogen responsible for tuberculosis, secretes a multitude of proteins that modulate the host's immune response to ensure its own persistence. The region of difference (RD) genes encoding proteins play key roles in TB immunity and pathogenesis. Nevertheless, the roles of the majority of RD‐encoded proteins remain to be elucidated. Objects To elucidate the role of Rv2652c located in RD13 in Mtb on bacterial growth, bacterial survival, and host immune response. Methods We constructed the strain MS_Rv2652c which over‐expresses Mtb RD‐encoding protein Rv2652c in M. smegmatis (MS), and compared it with the wild strain in the bacterial growth, bacterial survival, virulence of Rv2652c, and determined the effect of MS_Rv2652c on host immune response in macrophages. Results Rv2652c protein is located at cell wall of MS_Rv2652c strain and also an integral component of the Mtb H37Rv cell wall. Rv2652c can enhance the resistance of recombinant MS to various stressors. Moreover, Rv2652c inhibits host proinflammatory responses via modulation of the NF‐κB pathway, thereby promoting Mtb survival in vitro and in vivo. Conclusion Our data suggest that cell wall protein Rv2652c plays an important role in creating a favorable environment for bacterial survival by modulating host signals and could be established as a potential TB drug target.